ANALISIS GAYA BAHASA PERBANDINGAN DALAM NOVEL RUMAH UNTUK ALIE KARYA LENN LIU - halawa, Arnis Halawa; Abdul Malik; Tessa Dwi Leoni; Musliha; Asri Lolita; Siti Habiba (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the analysis of comparative language styles contained in the novel Rumah untuk Alie by Lenn Liu. The method used in this study is the researcher himself as the main instrument supported by data analysis guidelines. The data in this study are in the form of dialogue excerpts contained in the novel Rumah untuk Alie by Lenn Liu. Data collection techniques used to obtain research data are reading techniques, note-taking techniques, marking quotations, analyzing data into research tables, and concluding the results of the study. The data analysis techniques used are data reduction, data presentation, and data verification. The results of this study indicate the presence of ten types of comparative figures of speech, comprising a total af fifty-five data points seven instances of simile, nine of metaphor, nine of personification, three of depersonification, four of allegory, seven of antithesis, five of pleonasm, five of periphrasis, three of anticipation, and three of correction.